2008
DOI: 10.1186/1751-0147-50-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating β-endorphin, adrenocorticotrophic hormone and cortisol levels of stallions before and after short road transport: stress effect of different distances

Abstract: Background: Since transport evokes physiological adjustments that include endocrine responses, the objective of this study was to examine the responses of circulating β-endorphin, adrenocorticotrophic hormone (ACTH) and cortisol levels to transport stress in stallions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 47 publications
8
65
3
3
Order By: Relevance
“…Transport induced increased plasma and salivary cortisol concentrations in the studied cold-blood horses and was similar to that described by other researchers in warm-blood horses (Stull and Rodiek 2000, Fazio et al 2008a, Schmidt et al 2010a. The means of plasma cortisol concentrations were characterised by high SD values.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Transport induced increased plasma and salivary cortisol concentrations in the studied cold-blood horses and was similar to that described by other researchers in warm-blood horses (Stull and Rodiek 2000, Fazio et al 2008a, Schmidt et al 2010a. The means of plasma cortisol concentrations were characterised by high SD values.…”
Section: Discussionsupporting
confidence: 88%
“…The studied horses were transported under these conditions one hour or 12 hours, without significant differences in cortisol values measured immediately after transport. It should be mentioned that in other studies, the distance of transport also did not influence plasma or saliva Salivary and plasma cortisol in transported cold-blood horses W. Kędzierski et al Pferdeheilkunde 32 (2016) 493 cortisol concentrations determined just after the end of transport (Fazio et al 2008a, Schmidt et al 2010a. In fact, in a number of studies there was a significant increase in salivary or plasma cortisol concentrations only during the early stage of transport (Stull andRodiek 2000, Schmidt et al 2010a,b,c).…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, serum cortisol concentration slightly exceeded the upper value of normal range (Eades and Bounous, 1997) at all sampling times. The slightly higher than normal serum cortisol concentration in the blood sampled in the lairage might have been due to transport stress (Fazio et al, 2008;Werner and Gallo, 2008). There was a tendency for an increase in serum cortisol concentration at exsanguination; however, serum cortisol concentrations did not differ significantly among sampling times, which is in agreement with the study of Werner and Gallo (2008).…”
Section: Discussionsupporting
confidence: 86%
“…The authors concluded that HR is influenced by different sympathovagal mechanisms during stall rest, compared with the period during road transportation, and that HRV may be a sensitive indicator of stress in transported horses. β-endorphin, adrenocorticotrophic hormone (ACTH) and cortisol responses of 42 thoroughbred and crossbred stallions, before and after road transport to breeding stations over distances of 100, 200 and 300 km, were studied by Fazio et al (2008). All horses had previous trailering experience.…”
Section: Journey Timementioning
confidence: 99%